Electrical Conduction in Solution Grown Thin Films of the Complex of Fe(II) with Cyclodichlorophosphazene Trimer - SHARMA, H.K.; KUMAR, RAJESH (Asian Journal of Chemistry, 2010)
Current transport mechanism in thin films of the complex of Fe(II) with cyclodichloro phosphazene trimer (PNCl2)3 have been studied under normal and different illuminating conditions. It is found that at low fields film exhibit an ohmic behaviour and high field region is dominated by Poole-Frenkel (PF) type mechanism.